Celastrol Inhibits Canine Mammary Tumor Cells by Inducing Apoptosis via the Caspase Pathway - Ou, Guoxing; Jiang, Xianyu; Gao, Ang; Li, Xiaolong; Lin, Zijun; Pei, Shimin (Frontiers in Veterinary Science, 2022)
Canine mammary tumor is a serious disease threating the health of dogs and can be used as a research model for human breast cancer. The study of canine mammary tumor has a role of improving the welfare of dogs. Most common canine mammary tumor chemotherapy drugs have limited effects and drug resistance. Celastrol is an extract of Tripterygium wilfordii, which has a wide range of biological activities, including significant anti-tumor effects. At present, celastrol has not been used in the clinical treatment for canine mammary tumor. This study investigated the anti-tumor properties of celastrol through in vitro assay of cell proliferation inhibition, cell colony, cell migration and invasion; flow cytometry, qPCR and Western Blot methods were used to explore the anti-tumor mechanism of celastrol. The results show that celastrol can inhibit the proliferation of canine mammary tumor cells in vitro, and decrease the migration and invasion ability of canine mammary tumor cells. We also found that celastrol can upregulate Cleaved Caspase-3 and Cleaved Caspase-9 protein expression level to promote cell apoptosis, and can regulate cell cycle-related proteins to induce cell cycle arrest. In summary, celastrol may inhibit canine mammary tumor cells through the Caspase pathway, providing a new direction for anti-canine mammary tumor drugs, and is expected to become a new anti-cancer drug for canine mammary tumors.